If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(j-2)-3(1-j)=9(j+2)+1
We move all terms to the left:
8(j-2)-3(1-j)-(9(j+2)+1)=0
We add all the numbers together, and all the variables
8(j-2)-3(-1j+1)-(9(j+2)+1)=0
We multiply parentheses
8j+3j-(9(j+2)+1)-16-3=0
We calculate terms in parentheses: -(9(j+2)+1), so:We add all the numbers together, and all the variables
9(j+2)+1
We multiply parentheses
9j+18+1
We add all the numbers together, and all the variables
9j+19
Back to the equation:
-(9j+19)
11j-(9j+19)-19=0
We get rid of parentheses
11j-9j-19-19=0
We add all the numbers together, and all the variables
2j-38=0
We move all terms containing j to the left, all other terms to the right
2j=38
j=38/2
j=19
| 24=28-9x+13=-21 | | 31x+30=30x+10 | | 5(x-6)^2+7=32 | | 2a=a^2-5a | | 3x+-4Xx=12 | | 24=28-9x=-21 | | 9(2f-5)=3(4f+7) | | 4/5-7x=-6 | | 40x-10=-30x+40 | | 0=-5t^2+8t | | 0=3x^2-45x-42 | | 1p-120/2=90 | | a=a^2-5a | | 3x-22=2x+2 | | .20=1x+.25x | | a=a^2-a | | K-p=8 | | 13x=-12x | | 150÷3=x | | 30x+10=40x+8 | | 81=9×n | | 85=30q | | 112-t=85 | | 4x=12x=12/4x= | | -2f+7=9−f | | 4.6y=4600 | | -18+2c-16c=-9c+12 | | 4×n+21=85 | | w+15=47 | | -3x+9=4x+8 | | d-3,03=2 | | x2.5=10 |